PENGALAMAN KARYAWAN DAN ENGAGEMENT PASCA- PANDEMI DI INDUSTRI INDONESIA - Bahdin Nur Tanjung; Parlaban Karo-Karo; Imanuel Sembiring (Jurnal Industri Kreatif dan Inovatif, 2025)
This study examines significant changes in employee experience, employee engagement, and employee well-being in Indonesia’s industrial sector in the post-COVID-19 period. Using a qualitative conceptual approach through a systematic literature review, the research aims to analyze employees’ work experiences, assess engagement levels, and evaluate well-being across physical, mental, emotional, and social dimensions. Findings indicate a shift toward remote and hybrid work models, where about 83% of employees prefer this flexible arrangement. Nevertheless, the transition also brings challenges, including increased workload, heightened mental pressure, and declining well-being. The study identifies key factors influencing these three areas: adaptive leadership (e-leadership), organizational support (Perceived Organizational Support/POS), and the importance of digital transformation supported by employee training. The paper provides strategic recommendations for management to enhance employee experience, sustain engagement, and support employee well-being in the post-pandemic context.